Higher Order Thinking Skills (HOTS) Level Instructional Book of Arabic Language at Senior High School - Zubaidah, Zubaidah; Ainin, Moh.; Muassomah, Muassomah; Albantani, Azkia Muharom; Maimunah, Iffat (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
Textbooks are written with a focus on various aspects in order to keep up with developments and times and can implement the curriculum. HOTS is a high-level thinking skill teachers and students must possess in the 21st century. HOTS is an essential part of a textbook because textbooks are a learning medium. This study aims to determine the implementation of HOTS in textbooks and describe the instructions in the eleventh-grade Arabic textbook by Dariyadi and Feriandika. Various levels of instruction in a textbook are needed to determine student abilities, strengthen understanding, and evaluate and measure the goals achieved from a lesson. This research is literature research with a content analysis technique. The type of research data is primary data in the form of textbooks, data collection through documentation, verification, selection, focus, data, and then conclusion. The results showed that the Arabic textbook for class XI SMA had reflected HOTS with as much as 75% of HOTS-based exercises. The instructional level is at levels C4-C6 in analyzing, discovering, and creating.